2024
DOI: 10.1167/iovs.65.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Morphology and Photoreceptor Activity Are Related and Affected by Myopia Development

Reynolds Kwame Ablordeppey,
Carol Ren Lin,
Brian Song
et al.

Abstract: Purpose The choroid is critical for the regulation of eye growth and is involved in the pathogenesis of myopia-associated ocular complications. This study explores the relationship among choroidal biometry, photoreceptor activity, and myopic growth in marmosets ( Callithrix jacchus ) with lens-induced myopia. Methods A total of 34 common marmosets aged 92 to 273 days old were included in this study. Axial myopia was induced in 17 marmosets usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…The choroid provides vascular support to the outer retinal layer and is responsible for ocular temperature, intraocular pressure regulation, and light absorption [8]. In addition, it has been shown that it affects emmetropization [9]. The development of enhanced depth imaging-OCT has enabled us to investigate the thickness of the choroid in detail, which might be affected by many diseases [10].…”
Section: Introductionmentioning
confidence: 99%
“…The choroid provides vascular support to the outer retinal layer and is responsible for ocular temperature, intraocular pressure regulation, and light absorption [8]. In addition, it has been shown that it affects emmetropization [9]. The development of enhanced depth imaging-OCT has enabled us to investigate the thickness of the choroid in detail, which might be affected by many diseases [10].…”
Section: Introductionmentioning
confidence: 99%